The Association of Nutritional Status and Body Composition with Cardiorespiratory Fitness: A Literature Review: Ramadhana Komala, Wiwi Febriani - Komala, Ramadhana (Jurnal Kedokteran Universitas Lampung, 2025)
Cardiorespiratory fitness is influenced by multiple factors, including nutritional status and body composition, which determine the body’s ability to sustain physical activity. This literature review aims to analyze the relationship between nutritional status, body composition, and cardiorespiratory fitness based on studies published between 2015 and 2025. The findings show that excessive nutritional status, particularly obesity, increases physical load and reduces movement efficiency, leading to lower cardiorespiratory fitness. Obesity is also associated with low-grade inflammation that negatively affects muscle function and circulation. Conversely, undernutrition contributes to reduced fitness due to low muscle mass and limited energy reserves. Body composition is a key determinant, as high body fat—especially visceral fat—is consistently linked to poor cardiorespiratory fitness, whereas adequate muscle mass supports efficient oxygen use and better endurance. Overall, the highest levels of cardiorespiratory fitness are observed in individuals with normal nutritional status, low body fat, and optimal muscle mass. These findings highlight the importance of maintaining optimal nutritional status and body composition as essential strategies for improving health and fitness.